Proximate Analysis On Nile Tilapia Artificial Feed From Shrimp Waste - Nanda Fathia Saputri; Asha Arning Putri (Eduvest - Journal of Universal Studies, 2024)
Nile Tilapia (Oreochromis niloticus) is the most widely cultivated freshwater fish because it can grow well in tropical countries and temperate regions. This research aims to create artificial feed that matches the nutritional parameters needed by nile tilapia. This artificial feed will use the basic ingredients of shrimp waste, with addition of oilcake, bran, starch flour, vitamins, squid oil, and water. There are four variables used to make artificial feed with different basic and additional ingredients, as well as varied processing techniques. After artificial feed is completed, proximate analysis will be carried out to test composition of crude fiber, carbohydrates, water, fat, ash, and protein using various methods. The test method for the composition of crude fiber, carbohydrates, fat, ash, and protein follows the method set by the Association of Official Analytical Chemists (AOAC). Based on the results of proximate analysis, variable 1 (V1) has fulfilled the nutritional content of protein and moisture content needed by nile tilapia. This shows that artificial feed formulations from shrimp waste can be used because protein is an important element for nile tilapia growth, but the content of crude fiber, carbohydrates, fat, and ash exceeds ideal value for nile tilapia nutrition. This also occurs in variables 2, 3, and 4 that have not met nutritional needs, especially protein. However, the composition of artificial feed with shrimp waste and addition of meal, bran, starch flour, vitamins, and water in V1 can be further investigated to reduce the content of crude fiber, carbohydrates, fat, and ash.